Efficiency as a parameter for assessing the Polish healthcare system - Bogdan, Magdalena; Barańska, Agnieszka; Drop, Bartłomiej; Firlej, Ewelina; Bartczak, Krzysztof; Janiszewska, Mariola (Journal of Education, Health and Sport, 2018)
Introduction. Efficacy is defined as one of the most valid parameters of health system evaluation. It should be said that there is no consistent definition of the concept of effectiveness in health care, which would allow for the evaluation and comparison of health systems in the world. One can not point to the best or even near ideal of the health system. However, you can rank individual health systems with respect to the evaluation of individual parameters or groups of parameters. One of the possibilities is to evaluate the effectiveness of the system. Aim of the study. The aim of the article is to define and analyze particular types of system effectiveness in the context of the Polish health system. Description of knowledge. The literature on the subject is divided into operational and dynamic efficiency. Dynamic efficiency is divided into adaptive and innovative. The Polish health system is characterized by high operational efficiency. Operational efficiency determines the intensity of the system. The key factor for improving the health of the Polish society, as a factor of socio-economic development of the country is to improve the dynamic efficiency of the system. Conclusions. Health care in Poland has high operational efficiency while low dynamic efficiency, both adaptive and innovative, which clearly demonstrates the existence of a paradox of the overall effectiveness of the health care system in Poland.